Faktor Faktor yang Mempengaruhi Tingkat Permintaan Selain Harga di Pasar Induk Sangatta Utara - Nur Alya Amalia; Lucia Chandra Dewi; Muhammad Sainil Abidin; Novita Putri Rahayu (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aims to find out what factors can influence the level of demand other than price in the North Sangatta main market. This type of research is field research, with a qualitative descriptive approach. The data collection techniques used in this research are interviews, observation and documentation. The data analysis used in this research is qualitative descriptive, through several stages, the first stage is data reduction, the second stage is data presentation, and the final stage is drawing conclusions. The results of this research show that there are several factors that influence the level of demand from the consumer's point of view and the producer's point of view in the main market of North Sumatra. From the consumer's point of view, factors that influence the level of demand include the size and shape of goods or services, promotions and discounts, and income. monthly, from the producer's point of view, including consumer behavior (consumer tastes), quality of goods, certain seasons or weather, and prices of other goods.